2005
DOI: 10.1292/jvms.67.1089
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cellular Radiosensitivity from DNA Damage Induced by .GAMMA.-Rays and Carbon Ion Irradiation in Canine Tumor Cells

Abstract: ABSTRACT. Diseases of companion animals are shifting from infectious diseases to neoplasms (cancer), and since radiation therapy is one of the effective choices available for cancer treatment, the application of radiotherapy in veterinary medicine is likely to increase. However tumor tissues have different radiosensitivities, and therefore it is important to determine the intrinsic radiosensitivity of tumors in individual patients in advance of radiotherapy. We have studied the relationship between the survivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The results of the present study were consistent with a previous canine cell line study (21). Additionally, several other previous studies using human and rodent cells have demonstrated that high LET heavy ions are more effective for cell killing at identical physical absorbed doses as low LET radiation types (10)(11)(12)21,26). In general, a large number of complex clusters of DNA damage generated by high LET radiation would be more difficult to repair, resulting in more severe biological damage than that induced by low LET radiation (28,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study were consistent with a previous canine cell line study (21). Additionally, several other previous studies using human and rodent cells have demonstrated that high LET heavy ions are more effective for cell killing at identical physical absorbed doses as low LET radiation types (10)(11)(12)21,26). In general, a large number of complex clusters of DNA damage generated by high LET radiation would be more difficult to repair, resulting in more severe biological damage than that induced by low LET radiation (28,29).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study were consistent with a previous canine cell line study (21). Additionally, several other previous studies using human and rodent cells have demonstrated that high LET heavy ions are more effective for cell killing at identical physical absorbed doses as low LET radiation types (10)(11)(12)21,26).…”
Section: Discussionsupporting
confidence: 92%
“…Among other radiobiological factors, intrinsic radiation sensitivity of tumour cells represents a major component attributing to treatment outcome [3,[12][13][14]. Intrinsic cellular radiation sensitivity correlates with the number of residual unrepaired DNA double strand breaks (DSBs) [15][16][17]. Therefore, assessment of intrinsic radiation sensitivity through quantification of DNA DSBs has become increasingly utilized in translation cancer research [18][19][20].…”
mentioning
confidence: 99%
“…Radiation-induced cell death is attributed mainly to DNA damage (39). Wada et al (40) have reported that the residual DNA damage per Gy obtained by neutral SCGE assay was significantly correlated with SF2, in canine tumor cell lines. Bacová et al (41) have demonstrated the potential of SCGE assay in prediction of intrinsic radiosensitivity using human ovarian carcinoma cell lines.…”
Section: Scge Assaymentioning
confidence: 99%